Rancang Bangun Rangka Pencetak Bakso Dengan Kapasitas 250 Butir/Menit - Gusriady Syahputra; Nazaruddin Nazaruddin; Herisiswanto Herisiswanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Meatball molding machine is a tool used to shape meatballs automatically by using electric motor power. The design stage is consists of needs analysis, preparation of product technical specifications, design of product concepts to produce alternative product concepts, which are then selected concepts to be made. From the form of the concept to be made, static analysis is carried out on the mechanical components of the meatball molding machine frame, which includes stress, deformation due to loading, safety factor and the number of welded wire. Static analysis was carried out in two ways, namely by manual calculation and finite element analysis using Autodesk Inventor 2016 Student Edition Software. Based on the results of the static analysis, the results of the maximum pressure was 0.5274 MPa on rod 1, 0.7031 MPa on rod 2. Deformation length was equal to 0.008721 mm on rod 1, 0.00116 mm on rod 2. The Safety factor was occurred 43.6 in stem 1, 32.7 in stem 2. The welding wire was used 8.635 sticks. The cutting time of the required frame components was 5.76 minutes. Keywords: meatballs machine, frame, stress, welding